Electromagnetic coupling to a wire in a rectangular enclosure through an aperture - Xin, Mengwei. (2009)
Metallic enclosures are often used to prevent electromagnetic interference. The existence of aperture and wire-penetration on the enclosure wall has a significant effect on the enclosure’s shielding capability or the electromagnetic coupling between internal circuits and external interferences. This project studies on the shielding behavior of rectangular enclosure with a wire-penetration aperture below frequency of 1 GHz. Extensive simulations using Ansoft’s High Frequency Structure Simulator (HFSS) are carried out to explore the effect of penetrating wire by changing the wire’s location, dimension and shape. Based on detailed statistic reports and figures tabulated from HFSS, six guidelines for metallic shielding design are formulated.